SYNTHESIS AND STRUCTURAL PROPERTIES OF CNTs/PEEK COMPOSITE MATERIALS OBTAINED USING FUNCTIONALIZED CNTs - ZAILANI, NURUL HUDA (2012)
Incorporation of carbon nanotubes (CNTs) into a polymer matrix can provide structural materials with dramatically increased mechanical and electrical properties. These properties combined with their low density makes them useful for the transport industry, especially for aerospace structures, where the reduction of weight is one of the main goals in order to reduce fuel consumption. However, several limitations exist firstly related to the dispersion of nanotubes and their compatibility with the matrix and secondarily to the nature of the binding between nanotubes and the polymer chains. These setbacks need to be resolved prior to successful applications. In this work, two main approaches are considered for fabricating CNTs/poly(ether ether ketone) (PEEK) composites. In the first case, multiwalled carbon nanotubes (MWNTs) were functionalized with carboxyl group (-COOH) through oxidation process and then were incorporated in PEEK matrix using compression moulding process. In order to obtain a covalent linking between nanotubes and the matrix, another approach has been used based on the use of both chemically modified MWNTs and polymer. The attachment of oxidized MWNTs and sulphonated PEEK (SPEEK) was possible using a diamine as an interlinking molecule. Pristine MWNTs have been also embedded in polymer matrix without any surface modification and were used as a reference. Transmission electron microscopy (TEM), Field emission scanning electron microscopy (FE-SEM), Fourier transform infrared (FT-IR) and X-ray diffraction (XRD) were used for structural investigation of the composite systems. Thermogravimetric analysis (TGA), Differential scanning calorimetry (DSC) and tensile test were done to understand the overall behavior ofthe composites. FE-SEM reveals that the dispersion of MWNTs is improved after oxidation process and functionalization with SPEEK. XRD results concluded the improvement of crystallinity after the addition of MWNTs to PEEK matrix and were confirmed with DSC scans. The thermal properties studied using TGA explained no significant amendments indicating no effects of MWNTs on the thermal properties of PEEK. On top of that, mechanical properties which is tensile modulus decreases after addition of SPEEK-MWNTs revealing that use of bi-molecular molecule is not a suitable way to achieve a good dispersion ofMWNTs in the matrix. On the basis of the results from this research, it can be concluded that incorporation of SPEEK-MWNTs to PEEK material does not affect or improve the thermal and mechanical behavior. Hence, the author recommends further approach offabrication method ofthe composites before other uses are considered.